(untitled) (Journal of Management & Business, 2022)
This paper investigates differences in the use of information sources between green innovative firms and other innovative firms. Green innovation presents differences with respect to other innovations, which should result in a different perception of the relevance of information sources. Using data from the National Innovation Survey in its 2015-2016 and 2017-2018 versions, this issue is empirically examined through the estimation of Probit models for each of the sources considered in that survey. In general, green innovators give greater relevance to the use of informational sources, particularly sources referring to clients, professional associations, universities and higher education institutions, and the Internet, which is in line with the intrinsic characteristics of this type of innovation. From this, it is concluded that, in order to give sustainability to green innovation, a public policy approach is needed to provide platforms for the dissemination of knowledge to access the set of best practices at the international level.